Mechanisms of Nordamnacanthal-Induced Apoptosis in Breast Cancer Cell Lines (MCF-7) and Acute T-Lymphoblastic Leukimia (MOLT-4) - Ishak, Norsyafini (2011)
Nordamnacanthal, an anthraquinone extracted from the root of Morinda elliptica from Rubiaceae family has cytotoxic properties towards cancer cell lines and antitumor promoting activities. This study was conducted to determine the mechanisms of nordamnacanthal-induced apoptotic cell death in the breast cancer (MCF-7) and acute -lymphoblastic leukemia (MOLT-4) cell lines at the concentration that reduced 50% of number of viable cells as compared to the untreated sample (IC50) and that caused 50% of the total cell population underwent apoptosis (50% Apoptosis), inclusive of analysis on the cell viability, cell cycle, and the expression of Bcl-2, Bax, caspases (caspase-2,-3,-6,-8 and -9) and p53. Nordamnacanthal was found to be more cytotoxic towards MOLT-4 than MCF-7 with the IC50 value of 3.8 μg/ml and 54 μg/ml, respectively, as detected by using the trypan blue dye exclusion test. However, by using staining with acridine orange (AO) and propidium iodide (PI) nordamnacanthal caused 50% of the total cell population of MCF-7 and MOLT-4 to undergo apoptosis (50% Apoptosis) at 70 μg/ml and 15 μg/ml, respectively, as analyzed by using a fluorescence microscope.The nordamnacanthal-treated MCF-7 and MOLT-4 cells at both concentrations employed (IC50 and 50% Apoptosis) showed characteristics of apoptosis such as membrane blebbing, chromatin condensation in the nucleus and the formation of apoptotic bodies observed under an inverted light microscope. Cell cycle analysis by flow cytometry indicated that nordamnacanthal did arrest MCF-7 cells at the G2/M phase at both IC50 and 50% Apoptosis values. For MOLT-4, the cell cycle was arrested at G0/G1 and S phases. In the treatment at the IC50 value, significant downregulation (p<0.05) in the expression of Bcl-2 and Bax was only observed in MCF-7 as detected by using commercial kits of Enzyme-linked Immunosorbent Assay for Quantitative Detection of Human Bcl-2 and Human Bax Enzyme Immunometric Assay, respectively. All the caspases were not activated in both cell lines following the treatment (IC50) as analyzed by using ApoTargetTM Caspase Colorimetric Protease Assay kit. The expression of p53 reduced significantly(p<0.05) in MCF-7 but increased significantly (p<0.05) in MOLT-4. In the treatment at the 50% Apoptosis, significant own regulation (p<0.05) in the expression of Bcl-2 and Bax was also only observed in MCF-7. Caspase-2,-3 and -8 were found to be activated only in MCF-7. The expression of p53 reduced significantly (p<0.05) in MCF-7 only. Whereas, the expression of p53 increased significantly (p<0.05) in MOLT-4. Nordamnacanthal was found to be more cytotoxic towards MOLT-4 than MCF-7 cell line. At the IC50 value, induction of apoptosis involved down-regulation of Bcl-2 in MCF-7 and up-regulation of p53 in MOLT-4 cells, with no caspase activity detected for both cell lines. Meanwhile, at the 50% Apoptosis, incidence of the programmed cell death in MCF-7 involved down-regulation of Bcl-2 and activation of caspase-2, -3 and -8. On the other hand in MOLT-4, the apoptotic pathway is still unclear because it involved up-regulation of p53 protein only.